2007
DOI: 10.1177/0193841x07299247
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Costs of Preventive Interventions

Abstract: The goal of this article is to improve the practice and reporting of cost estimates of prevention programs. It reviews the steps in estimating the costs of an intervention and the principles that should guide estimation. The authors then review prior efforts to estimate intervention costs using a sample of well-known but diverse studies. Finally, the authors illustrate the principles with an example, the Family Bereavement Program. They conclude that example by discussing whether and how the costs of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 17 publications
1
50
0
Order By: Relevance
“…Four types of costs have been identified as important in analysing the costs of preventive interventions such as bereavement programs (Foster, Porter, Ayers, Kaplan, & Sandler, 2007). These are medical, nonmedical, productivity, and intangible costs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four types of costs have been identified as important in analysing the costs of preventive interventions such as bereavement programs (Foster, Porter, Ayers, Kaplan, & Sandler, 2007). These are medical, nonmedical, productivity, and intangible costs.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of productivity costs also may include the loss of capacity to perform tasks at home. Intangible costs are costs that are nonmonetary, such as stigma or loss of professional satisfaction, and are often extremely difficult to measure (e.g., Foster et al, 2007;Onrust et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…ICERs that consider the same outcome can be used to compare the same Importantly, they answer common questions posed by policy makers and budget writers [22,64]. Further, by undertaking these analyses, researchers can provide decision makers with accurate estimates as opposed to back-of-the-envelope analyses that may consider only tangible resources but neglect crucial personnel, volunteer, and in-kind resources [65]. Both cost and costeffectiveness analyses have limitations in their utility for informing decision makers.…”
Section: Economic Evaluationmentioning
confidence: 99%
“…7 Cost analyses of health care interventions are essential in today's ever-changing health care field to ensure quality care while health care costs continue to increase annually. 8,9 Therefore, the authors of this article propose that home delivery of chemotherapy is an example of a PC intervention that can improve the QOL of pediatric oncology patients, foster a cost savings plan, and also support the WHO definition of PC.…”
mentioning
confidence: 99%
“…Also, in several studies, investigators have reported that a major benefit of outpatient delivery of chemotherapy results in significant reduced health care costs (ie, due to decreased hospital admissions). 8,9,[11][12][13] Standard risk medulloblastoma (SRMB) patients spend approximately 14 months after diagnosis undergoing radiation and chemotherapy. Because survival has improved to almost 90%, 14 it is imperative to focus not only on the QOL of survivors but also on the patient's QOL while receiving oncology treatments.…”
mentioning
confidence: 99%